2013
DOI: 10.1111/clr.12284
|View full text |Cite
|
Sign up to set email alerts
|

Differences in degradation behavior of two non‐cross‐linked collagen barrier membranes: an in vitro and in vivo study

Abstract: This study shows differences in the biodegradation characteristics of two non-cross-linked collagen membranes in vitro and in vivo. Whether the higher stability of RX is of clinical relevance should be analyzed in future clinical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 30 publications
2
40
1
Order By: Relevance
“…This stain allows aligned (red) fibers to be distinguished from nonaligned (green) collagen fibers General and specific tissue reactions in three regions of interest (one at one end, one at the opposite end and one in the middle) according to Bozkurt et al . Details of the parameters evaluated and of the scoring system are presented in Table .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This stain allows aligned (red) fibers to be distinguished from nonaligned (green) collagen fibers General and specific tissue reactions in three regions of interest (one at one end, one at the opposite end and one in the middle) according to Bozkurt et al . Details of the parameters evaluated and of the scoring system are presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Details of the parameters evaluated and of the scoring system are presented in Table .
General and specific tissue reaction scores according to Bozkurt et al Parameters 7 days 14 days 30 days General tissue reactionFibrosis+Fatty infiltrate++Hemorrhage+++++NecrosisDegenerationForeign debrisNumber of blood vessels (SE)1.13 (1.55)7.50 (3.42)11 (11.38)Specific tissue reaction (score 0‐3 and SE)Polymorphonuclear leukocytes0.38 (0.58)0.25 (0.44)0.25 (0.53)Lympocytes0.17 (0.38)0.58 (0.65)0.42 (0.58)Eosinophils0.04 (0.20)Plasma cellsMacrophages0.04 (0.20)0.08 (0.28)0.04 (0.20)Multinucleated giant cells
The general tissue reaction was evaluated using the following scoring system: −, not present; +, present in ≥10% of the viewed area; ++, present in ≥20% of the viewed area; and +++, present in ≥50% of the viewed area. The number of blood vessels (and SE) in the extracranial and intracranial membranes of each sample was counted. The specific tissue reaction was evaluated using the following scoring system: 0, no cells; 0.5, <10 cells; 1, 10‐50 cells; 2, 50‐90 cells; and 3, >100 cells.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature exposure to the oral cavity is leading to early degradation and bacterial colonization compromising the beneficial effects of GTR or GBR procedures . The degradation rate may be influenced by various parameters such as the composition, structure, and dimensions of the membrane but also by systemic diseases, such as uncontrolled diabetes . In recent studies, CM degradation was found to be accelerated in uncontrolled diabetic rats .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a native collagen membrane with a significantly longer degradation time and increased mechanical properties, such as higher tensile and suture pull‐out strength, has been developed (Bozkurt et al. ). This membrane had a low membrane exposure rate (12%) in a retrospective analysis of 36 patients with simultaneous or subsequent implant placement (Wessing et al.…”
mentioning
confidence: 99%